Associations of sleep time, quality of life, and obesity indicators on physical literacy components: a structural equation model - Vanilson Batista Lemes; Ana Paula Sehn; Cézane Priscila Reuter; Ryan Donald Burns; Anelise Reis Gaya; Adroaldo Cesar Araujo Gaya; Caroline Brand (BMC, 2024)
Abstract Aim To verify the association between ideal sleep time and physical literacy components while also considering multiple mediators, such as quality of life and obesity, using a sample of adolescents. Methods This cross-sectional study consisted of 470 adolescents aged 11-17 years from southern Brazil. Sleep time, health-related quality of life, and physical literacy components (i.e., physical education enjoyment, sports participation, sedentary behavior, moderate to vigorous physical activity, sex, and age) were evaluated through self-reported questionnaires. In addition, body mass index (BMI), and waist circumference were determined. The theoretical/statistical support of the structural equation model was evaluated according to fit parameters and strength of association. Results A direct association was observed between more sleep time and lower levels of obesity. The obesity indicators also had a negative association with HqOL, and HqOL had a positive association with physical literacy. The indirect associations indicated that the ideal sleep time was positively associated with HqOL and physical literacy components, considering the negative mediation effect of obesity. The model explains physical literacy in 31% of the variance (R = 0.31). Conclusion There was an indirect association between ideal sleep duration and quality of life and between both variables with physical literacy. These relationships occur even considering the negative influence of obesity. Therefore, a child who sleeps adequately has a higher likelihood of being physically active, regardless of obesity, potentially enhancing overall quality of life across various domains.